2016
DOI: 10.1186/s40169-016-0121-6
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical study of Gene‐Eden‐VIR/Novirin in genital herpes: suppressive treatment safely decreases the duration of outbreaks in both severe and mild cases

Abstract: Background We conducted a clinical study that tested the effect of suppressive treatment with the botanical product Gene-Eden-VIR/Novirin on genital herpes. Our previous paper showed that the treatment decreased the number of genital herpes outbreaks without any side effects. It also showed that the clinical effects of Gene-Eden-VIR/Novirin are mostly better than those reported in the studies that tested acyclovir, valacyclovir, and famciclovir. The current paper reports the effect of suppressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The Editor of this journal has published this Expression of Concern to alert readers that, following publication of the article [1], it came to light that there were undeclared competing interests that have a direct impact on the article and the strength of its findings. In addition, post publication peer review has indicated that the conclusions may not be supported by the results due to methodological flaws in the study.…”
Section: Expression Of Concern: Clin Trans Med (2016) 5:40 101186/s4mentioning
confidence: 99%
“…The Editor of this journal has published this Expression of Concern to alert readers that, following publication of the article [1], it came to light that there were undeclared competing interests that have a direct impact on the article and the strength of its findings. In addition, post publication peer review has indicated that the conclusions may not be supported by the results due to methodological flaws in the study.…”
Section: Expression Of Concern: Clin Trans Med (2016) 5:40 101186/s4mentioning
confidence: 99%
“…A fourth clinical study showed that Gene-Eden-VIR/Novirin decreased the duration of genital herpes outbreaks. 18 …”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies showed that Gene-Eden-VIR/ Novirin is a safe and effective treatment against several viruses, including the human papillomavirus (HPV), herpes simplex virus (HSV), Epstein-Barr virus (EBV), human cytomegalovirus (HCMV), and hepatitis C virus (HCV). [11][12][13][14] In another study, Polansky et al suggested that the possible broad antiviral effects of Gene-Eden-VIR/Novirin may be mediated through the treatment's effect on the immune system. 15 In the next section, we review evidence on the effects of the Gene-Eden-VIR/Novirin ingredients on the betacoronaviruses family of viruses, and specifically, the SARS-CoV virus.…”
mentioning
confidence: 99%